(untitled) (Международный научный журнал «Инженер», 2026)
The increasing prevalence of vehicles with automatic transmission significantly impacts urban transport dynamics. This article examines the influence of automatic transmission vehicles on traffic flow speed in urban streets, focusing on their advantages and potential challenges. Through a combination of theoretical calculations, simulations, and empirical experiments, the impact of these vehicles on traffic flow speed and congestion levels is evaluated. The research aims to provide insights for urban planning and transportation management strategies.